Mixed Spatial and Movement Representations in the Primate Posterior Parietal Cortex - Hadjidimitrakis, Kostas; Bakola, Sophia; Wong, Yan T.; Hagan, Maureen A. (Frontiers in Neural Circuits, 2019)
The posterior parietal cortex of humans and non-human primates plays a key role in the sensory and motor transformations required to guide motor actions to objects of interest in the environment. Despite decades of research, the anatomical and functional organization of this region is still a matter of contention. It is generally accepted that specialized parietal subregions and their functional counterparts in the frontal cortex participate in distinct segregated networks related to eye, arm and hand movements. However, experimental evidence obtained primarily from single neuron recording studies in non-human primates has demonstrated a rich mixing of signals processed by parietal neurons, calling into question ideas for a strict functional specialization. Here, we present a brief account of this line of research together with the basic trends in the anatomical connectivity patterns of the parietal subregions. We review the evidence related to the functional communication between subregions of the posterior parietal cortex and describe progress towards using parietal neuron activity in neuroprosthetic applications. Recent literature suggests a role for the posterior parietal cortex not as a constellation of specialized functional subdomains, but as a dynamic network of sensorimotor loci that combine multiple signals and work in concert to guide motor behavior.